2019
DOI: 10.1002/nbm.4237
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography‐derived stiffness of the kidneys and its correlation with water perfusion

Abstract: Stiffness plays an important role in diagnosing renal fibrosis. However, kidney stiffness is altered by perfusion changes in many kidney diseases. Therefore, the aim of the current study is to determine the correlation of kidney stiffness with water intake. We hypothesize that kidney stiffness will increase with 1 L of water intake due to increased water perfusion to the kidneys. Additionally, stiffness of the kidneys will correlate with apparent diffusion coefficient (ADC) and fractional anisotropy (FA) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…An earlier study of our group shows that multifrequency MRE of the kidneys is improved when omitting any breathing command compared with breath‐hold MRE 25 . However, this case‐specific finding from a single subject was never reproduced or compared with other abdominal organs, as done in the present study. All protocols provided values in the range of published values of abdominal MRE (converting SWS to shear modulus by µ = SWS 2 · 1000 kg/m 3 ) 37‐39 or directly agreed with reported SWS values in that region 25,40 . The visible blurring of the magnitude images in free‐breathing MRE (see Figures 3‐6) suggests that stiffness values are strongly affected by breathing motion, which, however, is not the case.…”
Section: Discussionsupporting
confidence: 67%
“…An earlier study of our group shows that multifrequency MRE of the kidneys is improved when omitting any breathing command compared with breath‐hold MRE 25 . However, this case‐specific finding from a single subject was never reproduced or compared with other abdominal organs, as done in the present study. All protocols provided values in the range of published values of abdominal MRE (converting SWS to shear modulus by µ = SWS 2 · 1000 kg/m 3 ) 37‐39 or directly agreed with reported SWS values in that region 25,40 . The visible blurring of the magnitude images in free‐breathing MRE (see Figures 3‐6) suggests that stiffness values are strongly affected by breathing motion, which, however, is not the case.…”
Section: Discussionsupporting
confidence: 67%
“…For instance, it has been shown that liver stiffness increases with water ingestion and hepatic blood flow ( Ipek-Ugay et al, 2016 ; Tzschatzsch et al, 2016b ). The opposite effect, i.e., softening, has been observed in the pancreas and spleen ( Dittmann et al, 2017 ) while kidney stiffness has been reported to change only slightly with increasing bladder filling ( Gandhi et al, 2020 ) and hydration ( Marticorena Garcia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Water intake before a MRE scan can act also as a confounding factor to estimate the stiffness of kidneys. In a recent study, Gandhi et al observed a negative correlation between difference in stiffness values and changes in bladder volumes before and after water intake [67]. This suggests that at lower bladder volume the kidneys are still filtering the water where perfusion pressure is high leading to an increased stiffness in the kidneys.…”
Section: Influence Of Hydration On Renal Stiffnessmentioning
confidence: 96%
“…l While performing renal MRE, renal perfusion status should be taken into account to ensure reproducible detection [73]. Confounding stiffness changes due to excess water intake have been reported [67].…”
Section: Considerations Regarding Animal Preparation Lmentioning
confidence: 99%